Religious Education in Islamic and Christian Perspectives to Global Demands - Ahmad Hermawan (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2022)
Globalization challenges Muslims and Christians in developing religious education in Indonesia. The problem of globalization has attacked the teaching of spiritual values. The output of religious education has recently shifted from the primary goal of education because of a disoriented religious education system. Intolerance, corruption, human rights violations, and all forms of moral decay that the Indonesian people are currently facing are manifestations of Indonesia's lack of religious education. This study uses library research with a comparative study design to analyze and solve problems of religious education from both an Islamic and Christian perspective. This study finally resulted in developing religious education in the global era of Indonesia; cooperation between the government and religious education is needed, it is necessary to integrate spiritual values, and the positive values of globalization, interfaith and interfaith dialogue must be included as part of religious education. Religious education institutions must be separated from commercialization, and the development of cooperation between Christian and Islamic educational institutions must be implemented immediately.